Front Cover: Interactions of Plasmonic Silver Nanoparticles with High Energy Sites on Multi‐Faceted Rutile TiO2 Photoanodes (ChemCatChem 2/2020). Issue 2 (20th December 2019) - Ballestas‐Barrientos, Alfonso; Li, Xiaobo; Yick, Samuel; Yuen, Alexander; Masters, Anthony F.; Maschmeyer, Thomas
Abstract : The Front Cover shows the use of electron microscopy and spectroscopy to study the plasmonic enhancement in the photoelectrochemical activity of faceted rutile TiO2 photoanodes using silver nanoparticles. In their Full Paper, Prof. Thomas Maschmeyer and co‐workers used directing agents to promote the creation of active grain boundaries in rutile TiO2 thin films and optimise the further interaction with silver nanoparticles. Scanning electron microscopy using an Electron Backscatter Diffraction (EBSD) detector was used and the results were correlated with electrochemical impedance spectroscopy to reveal the optimised plasmonic interaction of silver on grain boundaries. An increase in the photoelectrochemical activity in the visible light‐stimulated photoelectrochemical activity was found. More information can be found in the Full Paper by Alfonso Ballestas‐Barrientos et al. on page 469 in Issue 2, 2020 (DOI: 10.1002/cctc.201901043 ).